Analisis Pengaruh Beban Kerja terhadap Tingkat Kelelahan Pekerja Karyawan Toko Menggunakan SSRT (Subjective Self Rating Test) dan CVL (Cardiovascular Load): Studi Kasus Toko Sarung Surya Baru - Afiano, Zhola Hamka; Suryadi, Akmal; Prameswari, Mega Cattleya (Ekonomis: Journal of Economics and Business, 2026)
This research aims to measure the workload and level of fatigue received by workers and determine the relationship between the two. The method used is %CVL to classify workload through the worker's pulse and the SSRT questionnaire to measure the level of worker fatigue through subjective assessment. Measurements of workload and fatigue levels were carried out on 30 respondents. This research is expected to contribute to improving the influence of workload to make it more ergonomic and help Toko Surya Baru Surabaya control the risk of health problems caused by ergonomic factors. By identifying the problem of employee work fatigue, Toko Surya Baru Surabaya can implement work improvement proposals to overcome employee fatigue that are more ergonomic to improve employee comfort and health.